Freak the Mighty - Philbrick, W. R. (W. Rodman) (New York : Scholastic, 1993)
At the beginning of eighth grade, learning disabled Max and his new friend Freak, whose birth defect has affected his body but not his brilliant mind, find that when they combine forces they make a powerful team.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
6.3
5-8
Keywords: Friendship -- Fiction; Learning disabilities -- Fiction; People with disabilities -- Fiction; Friendship -- Fiction; Learning disabilities -- Fiction; Physically handicapped -- Fiction